Quality of care and volume for patients with diabetes mellitus in the primary care setting: A population based retrospective cohort study. (October 2016) - Wong, Carlos K.H.; Fung, Colman S.C.; Kung, Kenny; Wan, Eric Y.F.; Yu, Esther Y.T.; Chan, Anca K.C.; Lam, Cindy L.K.
Abstract: Aims: To examine the association of patient volume with quality of diabetes care in the primary care setting. Methods: We analyzed population-based data from Hospital Authority administrative database using a Hong Kong representative sample of 187, 031 diabetic patients managed in 74 primary care general outpatient clinics between 04/2011 and 03/2012. We assessed the associations between annual clinic-based patient volume and quality of care in terms of adherence to care criteria of process (HbA1c test, renal function test, full lipid profile, urine protein analysis, diabetic retinopathy screening, and appropriate drug prescription) and clinical outcomes (HbA1c ⩽ 7%, BP ⩽ 130/80 mmHg, LDL-C ⩽ 2.6 mmol/L) of care criteria, with and without adjustment for patient and clinic characteristics. Results: Patient volume was associated with three of seven process of care criteria; however, when compared to clinics in higher volume quartiles, those in lowest-volume quartile had more odds of HbA1c test (odds ratios (OR): 0.781, 0.655 and 0.646 for quartile from 2 to 4, respectively), renal function test (OR: 0.357, 0.367 and 0.590 for quartile from 2 to 4, respectively), and full lipid profile test (OR: 0.508, 0.612 and 0.793 for quartile from 2 to 4, respectively). There was no significant association between patient volume and the standards of achieving of HbA1c, BP and LDL-C outcome targets. Conclusions: Disparities in volume and quality of diabetes care were observed in public primary care setting. Lower patient volumes at clinic level were associated with greater adherence to three process criteria but a volume–outcome association was not present.